ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - PRANTIGO, RAFLY (Fakultas Ekonomi Universitas Tadulako, 2016)
This research predicts the potential of bankruptcy of plantation sub-sector companies listed on BEI (Indonesia Stock Exchange) in 2012 to 2015. This research uses Altman Z-score analysis method and analyzes financial statements of 11 plantation sub-sector companies listed on The Indonesia Stock Exchange. The financial statements of 2012-2015 are taken from the official website of The Indonesia Stock Exchange (BEI) and then analyzed by using Altman Z-Score model for non-manufacturing company. Altman uses four financial ratios known as Z-Score with formulation Z = 6.56X1 + 3,26X2+ 6,72X3 + 1,05X4; Z-Score >2.6 indicates the company is healthy, 1.1 <Z-Score < 2.6 means companies are in the gray area, and Z-Score <1.1 means the company is predicted in bankruptcy. This research is a descriptive using 11 samples of plantation sub-sector companies listed on the Indonesia Stock Exchange with observation period from 2012 to 2015. The results show that in 2015 there are 2 (two) companies predicted healthy, 1(one) is predicted in the gray area and 8 (eight) companies predicted bankrupt. Astra Agro Lestari Tbk. (AALI) and PP London Sumatera Indonesia Tbk. (LSIP) are two companies that predictably healthy during the observation period.